Anionic polyacrylamide as an additive to prevent soil proneness towards land degradation leading to slope instabilities - Frutaz, Giulia; Bordoni, Massimiliano; Meisina, Claudia (Italian journal of engineering geology and environment, 2024)
Climate change and the intensification of extreme weather events constantly pose new threats to all human activities, damaging roads and communication networks, as well as economical activities and threatening human lives. Recently new materials are being considered as potentially useful tools in the prevention of land degradation leading to slope instabilities; among them polymers such as anionic polyacrylamide (PAM) are gaining more and more interest. PAM is known and employed as an additive in agriculture, in the prevention of irrigation-connected erosion, to maximize irrigation and fertilization efficiency and to enhance agricultural yield. Samples were reconstructed in laboratory using kaolin clay and silty sand, respectively, without mixing them to observe the effects of application of anionic polyacrylamide (PAM) on their physical, volumetric, mechanical, and hydrological properties. Fixed values were dry density (1.2 g/cm3 for kaolin clay and 1.4 g/cm3 for silty sand), initial water content (20% and 25% respectively) and polymer application rates (moving from the original 0%, 0.003%, 0.03%, 0.3%, 1% by weight for both “parent materials” to 0.01%, 0.03% and 0.05% for kaolin clay and 0.1%, 0.3% and 0.5% for silty sand, based on the results of previous analysis). Additional samples consisting of kaolin clay and quartz powder and polyacrylamide (with a concentration of 5% and 50%) were reconstituted specifically for ESEM analysis. The polymer, a granular anionic polyacrylamide provided by Micronizzazione Innovativa Srl, has been manually applied and mixed with the samples, reconstituted in pvc cylinders with a diameter of 9.5 cm and 5 cm high (although some were reconstituted in different cases for specific tests). Samples were then submitted to Atterberg limits with different curing times, hyprop and filter paper tests, WP4C, shear tests, and the record of volumetric characteristics. Results showed that the increase of PAM percentage in samples generally coincided with a widening of samples plasticity range, as well as with the increase of liquid limit and plasticity index; PAM influence was also a matter of time, being more relevant few days after the treatment and then slowly decreasing. Rise in PAM percentage coincided with an increase in samples porosity, and with a higher water retention, although it was impossible to identify a polymer characteristic structure with SEM analysis. These results can shed light on the potential application of polymers such as anionic polyacrylamide as a useful additive for the improvement of soil characteristics that impact on soil stability, in a frame of sustainable solutions for reduction of landslides susceptibility, hazard and risk.